Gelatins from Liza aurata skin: Structural characterization, in vitro and in vivo validation of acceleration epithelialization and cyto-protective effects. (October 2018) - Bkhairia, Intidhar; Bardaa, Sana; Ktari, Naourez; Ben Abdallah Kolsi, Rihab; Kallel, Rim; Zghal, Slim; Ben Salah, Riadh; Nasri, Moncef
Abstract: This paper provides results from a comprehensive experimental characterization on two gelatins extracted from golden grey mullet skin (GGSGs) with (5 U/g of skin) and without acid protease from the same specie. In view of their possible applications in medical engineering, GGSGs could be used as substrates for mechanobiological studies and wound healing. The resulting gelatins were structurally characterized by optical microscopy, differential scanning calorimetry (DSC), as well as by X-ray diffraction (XRD) and nuclearmagnetic resonance (NMR) spectroscopies. According to optical micrographs, DSC analysis, and XRD spectra, GGSGs are semi-crystalline polymers. Antioxidant activities of GGSGs were evaluated by five different methods in-vitro . GGSGs acted as a strong free-radical scavengers and they effectively protected skin genomic DNA against hydroxyl radical-induced oxidative damage. In addition, the wound healing efficiency of the GGSGs was assessed on circular excision wound rat model. GGSGs exhibited remarkable wound healing properties with 100% reduction of the wound area within 14 days. Histological examination also demonstrated a fully re-epithelialized wound with epidermal regeneration. These evidences depicted that GGSGs can be an ideal biomaterial for enhanced wound-healing effect presumably achieved through their antioxidant properties. Highlights: Gelatins (GGSG0 and GGSG5 ) were extracted from the skin of golden grey mullet. GGSGs are a semi-crystalline polymers by optical micrographs, XRD and DSC analysis. GGSGs showed antioxidant property. GGSGs enhanced wound healing activity. GGSG5 could be a potential therapeutic agent for treating dermal injury.